CLIFF-GRADS Science Series 2020 - Special Session: Special Session: WFO Young Farmers Panel - Knox, Deborah; Volpe, Luisa; Crofoot, Sarah; Bower, Richard; Tlhabane, Brenda (Global Research Alliance on Agricultural Greenhouse Gases (GRA) & CGIAR Research Program on Climate Change Agriculture and Food Security (CCAFS), 2020)
Featuring a panel of young farmers from the World Farmer Organization Gymnasium Programme.